Facile deoxygenation of amine-N-oxides with CoCl2 center dot 6H(2)O-indium system - Han, JH; Choi, KI; Kim, JH; Yoon, CM; Yoo, BW (TAYLOR & FRANCIS INC, 2006)
CoCl2 center dot 6H(2)O/In system was found to be a new reagent for deoxygenation of various amine- N -oxides to the corresponding amines in good to excellent yields under sonication.
Keywords: EFFICIENT DEOXYGENATION; CHEMOSELECTIVE DEOXYGENATION; REDUCTION; MILD; FORMATE; COBALT